An economic analysis of production and marketing of cashew nuts in Kallakurichi district - Gayathry, M; Parimalarangan, R; Saravanakumar, V; Moghana, L S; Arulselvi, S; Gurunathan , S (Plant Science Today, 2025)
India is the second-largest producer of cashew nuts in the world and Tamil Nadu is one of the major producers and exporters of cashew nuts in India. Kallakurichi is one of the districts in Tamil Nadu, where cashew is being cultivated and processed. This study focuses on the production and marketing of cashews in the Kallakurichi district, where no studies have been conducted. For this study, 30 farmers, 5 local traders, 5 processors, 5 wholesalers, 5 retailers and 5 consumers were interviewed. This study involves the estimation of economic aspects of raw cashew nut production by studying the cost and returns from the crop per unit of land. Percentage analysis was carried out to examine the cost that contributes more to the total cost and, therefore, to make suggestions to reduce the cost. Market study involved tracing the marketing channels of cashew nut in the district and estimating the marketing aspects, such as marketing cost, market margin, price spread and marketing costs were computed for each channel to ascertain the channel that involves the least cost in comparison with others. VRI 3 variety is extensively cultivated in the area. The study shows that the annual variable cost is ₹47105.5 per acre in the study area, while net returns over variable costs are ₹15830.58 per acre. Analysis of profitability showed that NPV, BCR and IRR are ₹3542.89, 1.07 and 12.80 % respectively. Sensitivity analysis revealed that cashew cultivation is highly sensitive to fluctuations in costs. There are five marketing channels for marketing raw cashew nuts. Among the channels, Channel III (Farmer-Processor-Consumer) involves minimum cost and maximum efficiency in comparison with other channels. Constraints in production and marketing were also studied. Among the variable costs, the cost of harvesting was higher, which was because harvesting was the most labour-intensive process. The major constraint in production was uncertain weather, which led to fluctuations in yield and price.